Cytochrome P450 2015
DOI: 10.1007/978-3-319-12108-6_7
|View full text |Cite
|
Sign up to set email alerts
|

P450s in Plants, Insects, and Their Fungal Pathogens

Abstract: IntroductionCytochrome P450 monooxygenases (P450s) are integral components in pathways producing metabolites important for normal growth and development as well as for adaptive strategies that define biotic interactions, including trophic interactions between plants, insects, mammals, fish, and their respective pathogens Biosynthetic P450s in these pathways can be considered organism-general (fatty acids, sterols) versus organism-specific with examples of the latter including structural components (plant cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 363 publications
0
31
0
Order By: Relevance
“…Previous studies have focused on the role of P450s in the detoxification of intracellular and xenobiotic compounds . Several P450s are implicated in the degradation of caffeine, and the up‐regulation of Cyp4e3 in the Malpighian tubules is associated with permethrin resistance and surmised to impact cellular response to stress .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused on the role of P450s in the detoxification of intracellular and xenobiotic compounds . Several P450s are implicated in the degradation of caffeine, and the up‐regulation of Cyp4e3 in the Malpighian tubules is associated with permethrin resistance and surmised to impact cellular response to stress .…”
Section: Introductionmentioning
confidence: 99%
“…22 Previous studies have focused on the role of P450s in the detoxification of intracellular and xenobiotic compounds. [23][24][25][26] Several P450s are implicated in the degradation of caffeine, 27 and the up-regulation of Cyp4e3 in the Malpighian tubules is associated with permethrin resistance and surmised to impact cellular response to stress. 28 To date, the functional role of the Cyp6g1 gene has been particularly focused upon in order to identify the mechanism by which this P450 metabolizes insecticides in D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Since their identification five decades ago, quite a large number of P450s have been identified in species across biological kingdoms, especially due to the current genome sequencing rush 2 . Studies on P450 enzymes have been reported from animals owing to their role in drug metabolism (particularly from mammals) 3 or analysis of diversity 1 4 ; from fungi owing to their role as drug targets 5 6 and for evolutionary analysis 7 8 9 ; from bacteria owing to P450 structure-functional analysis 10 and generation of products valuable to humans 11 ; and from plants owing to their roles in key cellular processes and defense mechanisms 12 13 14 . Irrespective of their origins, P450s from all organisms have been exploited for their biotechnological potential 15 .…”
mentioning
confidence: 99%
“…Genomes of higher plants contain a large number of P450s. For example, the Arabidopsis (Arabidopsis thaliana) genome encodes 246 full-length P450s, accounting for approximately 1% of the Arabidopsis gene complement, and the Jatropha curcas (Barbados nut) genome is estimated to encode greater than 400 P450s (Schuler, 2015). Plant P450s have been shown to participate in a variety of pathways, including the biosynthesis of phenylpropanoids, alkaloids, terpenoids, lipids, cyanogenic glycosides, and glucosinolates, as well as plant growth regulators such as auxin, gibberellins, jasmonic acid, and brassinosteroids.…”
Section: Cytochrome P450smentioning
confidence: 99%
“…1B; Box 1), control of the reaction outcome by nonhydroxylating members is a continuing field of study. Many characterized plant P450s catalyze hydroxylation (Schuler, 2015) of sp 3 or sp 2 C-H bonds, but their arsenal of catalysis is continually expanding as new plant natural product chemistry is discovered. P450 hydroxylases typically display strong preference toward a selective C-H bond of their substrate, but many have been shown to exhibit a general promiscuity, catalyzing a small percentage of altered regiospecific outcomes and/or activity upon related chemical scaffolds.…”
Section: Cytochrome P450smentioning
confidence: 99%